Development and Experimental Investigation of Composite Structure Heat Pipe - Jadav, Rivaan; Mehta, Aashay; Bhatt, Soham; Parikh, Hiral (Recent Innovations in Chemical Engineering, 2023)
Aim: This study aimed at developing a composite structure heat pipe. Background: Conventionally, the heat pipe enclosure is made out of a single continuous conductive material corresponding to minor heat losses to the surrounding through the middle section, which ideally needs to be adiabatic in nature. The insulating nature of the carbon fiber reduces the axial heat losses and improves the latent heat of vaporization. Objective: The objective of this study is to develop a carbon fiber-reinforced composite heat pipe and a test rig to check the performance of the heat pipe. Methods: The hand lay-up technique is used to develop a composite structure heat pipe with a carbon fiber adiabatic section. A test rig is developed to check the performance of the heat pipe. Moreover, the weight comparison is made for a conventional and composite structure heat pipe. Results: The test results reveal that the composite structure heat pipe gives weight reduction in the range of 25 to 30 percent than the conventional heat pipe for identical dimensions and also shows a faster heat absorption rate. Conclusion: Conventional heat pipe may be replaced with the lightweight composite structure heat pipe.
Keywords: carbon fiber